Short-term impact of COVID-19 on financial system in a dollarized economy - Segundo Camino-Mogro (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
This paper analyzes the short-term impact of the lockdown policies implemented to stop the spread of the COVID-19 on the Ecuadorian financial system. We use a regression discontinuity in time (RDiT) design jointly with official data. Results show an overall decrease in total deposits (-3.4%) as well as in credits targeted to private sector (-0.60%). In addition, we find heterogeneous results across the different types of credits and deposits being the most affected those related to public institutions.
Keywords: G21; G51; H12; 330; COVID-19; lockdown; financial system; regression discontinuity; Ecuador